Psychometric properties of the translated Spanish version of the Pain Self-Efficacy Questionnaire - Perez-Dominguez, Borja; Perpiña-Martinez, Sara; Escobio-Prieto, Isabel; de la Fuente-Costa, Marta; Rodriguez-Rodriguez, Alvaro Manuel; Blanco-Diaz, Maria (Frontiers in Medicine, 2023)
Introduction: Some patients with rotator cuff injuries do not report significant changes in pain-related outcomes. Pain self-efficacy, which is commonly assessed using the Pain Self-Efficacy Questionnaire, may contribute towards this outcome. However, a Spanish adaptation of this questionnaire is currently lacking. Therefore, this study's purpose was developing the Spanish version of this questionnaire, and assess its psychometric properties. Methods: The Spanish version of the Pain Self-Efficacy Questionnaire was translated and culturally adapted, and a sample of 107 patients with rotator cuff injuries completed the questionnaire to examine its convergent validity (analyzing its correlation with the Tampa Scale of Kinesiophobia), its test-retest reliability, for which a subset of 40 participants completed again the questionnaire, and its internal consistency; Results: Translation was conducted without any problems, and 107 participants completed the study. Mean scores for the Pain Self-Efficacy Questionnaire were 45.2 points (standard deviation, 11.4). The Pain Self-Efficacy Questionnaire showed a moderate negative correlation with the Tampa Scale of Kinesiophobia (Pearson's correlation index r=-0.48) supporting its convergent validity. High testretest reliability (Intraclass Correlation Coefficient of 0.90) and excellent internal consistency (Cronbach's α value of 0.92) were also found; Discussion: The Spanish version of the Pain Self-Efficacy Questionnaire presents high validity, test-retest reliability, and internal consistency to assess pain self-efficacy in patients suffering rotator cuff injuries in Spanish-speaking settings.